The Role of Technology in the Evaluation of Islamic Religious Education Learning - Halimah, Siti; Jannah, Indana Roichatul; Setyawati, Nanik; Muharroroh, Maryam (AR-RASYID : Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the role of technology in improving the effectiveness and efficiency of Islamic Religious Education (PAI) learning evaluation in the digital era. The focus of the research is on how the application of digital media and platforms, such as Learning Management Systems (LMS), Google Forms, and Quizizz, can enhance the interactivity, objectivity, and relevance of modern learning assessment. The research employs a qualitative descriptive method using a library research approach by reviewing relevant journals, books, and previous studies concerning the use of technology in PAI learning evaluation. The findings reveal that technology improves feedback accuracy and timeliness, broadens access to learning outcome data, and encourages students’ active participation. Nevertheless, several challenges were identified, including low digital literacy among teachers and students, limited infrastructure, and data security concerns. This study emphasizes the importance of enhancing teachers’ digital competence and providing adequate technological facilities to ensure that digital-based evaluation can be effectively and sustainably implemented in Islamic education contexts.